FUNKCJONOWANIE AUTOMATYCZNYCH STABILIZATORÓW KONIUNKTURY NA PRZYKŁADZIE REPUBLIKI FEDERALNEJ NIEMIEC W LATACH 1980-1998 - Krajewski, Adam (Wydział Prawa i Administracji UAM, 2005)
The article assesses to what extent various components of government budgets affected by the macroeconomic situation operate (through influencing domestic demand) to smooth the business cycle1 in Germany. The aim of the research is to evaluate government budget sensitivity to economic fluctuations and thereby assess the importance of automatic fiscal stabilisers. Fiscal policies and the analysis of fiscal stabilisers have been added to the agenda due to the fact that the EMU member countries no longer have national monetary policies at their disposal and therefore fiscal policy has to play a more important role in smoothing shocks, especially if they originate on the demand side. However, in order to avoid the typical pitfalls of fiscal finetuning, the main focus has increasingly been put on the work of automatic stabilisers. This view is codified in the Stability and Growth Pact, whose “fiscal philosophy” implies that countries should set a structural target of close to balance or surplus and simply let automatic stabilisers work, where appropriate, over the whole business cycle without breaching the 3% reference value for the deficit. To determine the size of budgetary cyclical components, i.e. the size of automatic fiscal stabilisers and the structural balance, the standard two-step procedure (also followed by the OECD, the IMF and the European Commission) was used. The first stage of this method is to measure the GDP gap, which is needed for both, estimating budget sensitivity and extracting a budget cyclical component. In line with the method of the European Commission, the estimate of the GDP gap is based upon a statistical smoothing technique (the Hodrick-Prescott filter). The Hodrick-Prescott filter (HP-filter) has been selected on the basis of pragmatic criteria such as simplicity and transparency. The second stage is to identify the cyclical sensitivity of all budget components (on the revenue and expenditure side2) - their sensitivity to the GDP gap. Finally, budget’s cyclical component and structural balance are both calculated on the basis of sensitivity estimates and the GDP gap. It is well known that the automatic fiscal stabilisers generally reduced cyclical volatility in the 1990s, although they were growing weak, while discretionary fiscal policy became more active. However, in Germany the need to undertake fiscal consolidation in order to improve public finances forced governments to take discretionary actions that in effect reduced, or even offset, the effect of automatic fiscal stabilisers. Based on data from 1980 until 1998 and using the two-step method, the cyclical sensitivity of the German budget was found to be only 0,35. This means that when the GDP diverges from its potential value by 1%, the budget balance will change accordingly by up to 0,35% of the GDP.
FUNCTIONING OF AUTOMATIC FISCAL STABILISERS IN GERMANY IN 1980-1998